Positive association between hypertension and urinary bladder cancer: epidemiologic evidence involving 79, 236 propensity score-matched individuals. (3rd April 2018) - Kok, Victor C.; Zhang, Han-Wei; Lin, Chin-Teng; Huang, Shih-Chung; Wu, Ming-Feng
Abstract: Introduction: We hypothesized that hypertensive patients harbor a higher risk of urinary bladder (UB) cancer. Material and methods: We performed a population-based cohort study on adults using a National Health Insurance Research Database (NHIRD) dataset. Hypertension and comparison non-hypertensive (COMP) groups comprising 39, 618 patients each were propensity score-matched by age, sex, index date, and medical comorbidities. The outcome was incident UB cancer validated using procedure codes. We constructed multivariable Cox models to derive adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs). Cumulative incidence was compared using a log-rank test. Results: During a total follow-up duration of 380, 525 and 372, 020 person-years in the hypertension and COMP groups, 248 and 186 patients developed UB cancer, respectively, representing a 32% increase in the risk (aHR, 1.32; 95% CI, 1.09–1.60). Hypertensive women harbored a significantly increased risk of UB cancer (aHR, 1.55; 95% CI, 1.12–2.13) compared with non-hypertensive women, whereas men with hypertension had a statistically non-significant increased risk (aHR, 1.22; 95% CI, 0.96–1.55). The sensitivity analysis demonstrated that the increased risk was sustained throughout different follow-up durations for the entire cohort; a statistical increase in the risk was also noted among hypertensive men. Conclusion: This nationwide population-based propensity score-matched cohort study supports a positive association between hypertension and subsequent UB cancer development.